2020
DOI: 10.1007/s00394-020-02324-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gut microbiota in the pathogenesis of coeliac disease and potential therapeutic implications

Abstract: Purpose Although genetic predisposition and exposure to dietary gluten are considered necessary triggers for the development of coeliac disease, alterations in the gut microbial composition may also contribute towards the pathogenesis of coeliac disease. This review aims to provide an overview of the available data on the potential mechanisms through which the gut microbiota plays a role in the causation of coeliac disease and to discuss the potential therapeutic strategies that could diminish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 203 publications
(249 reference statements)
0
35
0
Order By: Relevance
“…Coeliac disease, prevalent in 1–2% of the global population, is an immune-mediated inflammatory disorder that primarily affects the small intestine and is initiated following ingestion of gluten in genetically predisposed individuals [ 189 , 190 ]. Research has suggested that dysbiosis plays a role in triggering coeliac disease with a dysregulated immune response and failure to maintain intestinal barrier integrity, leading to mucosal inflammation [ 191 ]. However, like IBD, it remains unclear as to whether the dysbiotic state characteristic of coeliac disease is a cause or consequence of a dysregulated immune response.…”
Section: Dysbiosis and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Coeliac disease, prevalent in 1–2% of the global population, is an immune-mediated inflammatory disorder that primarily affects the small intestine and is initiated following ingestion of gluten in genetically predisposed individuals [ 189 , 190 ]. Research has suggested that dysbiosis plays a role in triggering coeliac disease with a dysregulated immune response and failure to maintain intestinal barrier integrity, leading to mucosal inflammation [ 191 ]. However, like IBD, it remains unclear as to whether the dysbiotic state characteristic of coeliac disease is a cause or consequence of a dysregulated immune response.…”
Section: Dysbiosis and Diseasementioning
confidence: 99%
“…As coeliac disease generally presents in childhood and young adulthood, most studies looking at a link between coeliac disease and the microbiome have focused on children [ 191 ]. Rod-shaped bacteria, including Clostridia, Provotella, and Actinomyces, are more frequently found in the small bowel of children with active coeliac compared with healthy controls [ 192 ].…”
Section: Dysbiosis and Diseasementioning
confidence: 99%
“…Celiac disease (celiac disease) is the only autoimmune disease in which both the trigger, the epigenetic factor (gluten), but also the specific HLA antigen (human leukocyte antigen) are known. Unfortunately, celiac disease is underdiagnosed, and people with or without GI manifestations, symptomatic and asymptomatic subjects can be found [ 52 ]. Dysbiosis can promote celiac disease, and recent studies have established a link between dietary gluten (wheat, oats, barley, rye) and changes in the intestinal microbiome.…”
Section: Effectiveness In Promoting Health: Mechanism Of Action Ofmentioning
confidence: 99%
“…An imbalance of the gut microbiota composition, called microbial dysbiosis, is characterized by decreased microbial diversity, gain or loss of specific community members or changes in their relative abundance [ 49 ]. A wide array of studies have identified significant differences in the microbial diversity and taxonomic composition of gut microbial communities between healthy controls and patients with CD [ 44 , 50 , 51 , 52 ] or T1DM [ 53 , 54 , 55 ]. However, the specific microbial taxonomic differences vary widely depending on the study design, and a definitive disease-associated community structure has not been identified.…”
Section: Discussionmentioning
confidence: 99%